2020
DOI: 10.1039/d0ra08298h
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural study of epoxy-based thermosets prepared by “classical” and cationic frontal polymerization

Abstract: Epoxides prepared by cationic frontal polymerization have a greater reduced void fraction than “classically” cured samples revealing free-volume consequences of waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…3,35 RICFP thus far has been studied as a method to frontally polymerize epoxide monomers. [44][45][46][47][48][49][50][51][52][53][54] There has been recent work showing RICFP of pure divinyl ethers and divinyl ether/epoxy/acrylate hybrid systems with nearinfrared sensitizers added to promote front initiation via near-infrared laser as well. 55 Use of vinyl ethers in small concentrations with pyrylium salts as a coinitiator system for photoinduced thermal FP has also been shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,35 RICFP thus far has been studied as a method to frontally polymerize epoxide monomers. [44][45][46][47][48][49][50][51][52][53][54] There has been recent work showing RICFP of pure divinyl ethers and divinyl ether/epoxy/acrylate hybrid systems with nearinfrared sensitizers added to promote front initiation via near-infrared laser as well. 55 Use of vinyl ethers in small concentrations with pyrylium salts as a coinitiator system for photoinduced thermal FP has also been shown.…”
Section: Introductionmentioning
confidence: 99%
“…RICFP thus far has been studied as a method to frontally polymerize epoxide monomers 44–54 . There has been recent work showing RICFP of pure divinyl ethers and divinyl ether/epoxy/acrylate hybrid systems with near‐infrared sensitizers added to promote front initiation via near‐infrared laser as well 55 .…”
Section: Introductionmentioning
confidence: 99%
“…133 Photo-induced RICFP was also compared with "classically" thermally induced RICFP. 136 This investigation revealed that the phototriggered propagation is twice as fast as the thermally induced one with a comparable maximal reaction temperature and heat conductivity. Additionally, materials obtained with thermally-induced RICFP exhibit high microstructural heterogeneity, which confirmed the photo-induced process's predominance.…”
Section: Reviewmentioning
confidence: 77%
“…From the T max values, reported in Table 1, it is evident that the thermal fronts reached a very high temperature, up to 285°C, similar to the values previously reported for the RICFP of DGEBA with TPED and PAG (283°C). [51] To investigate the photo-crosslinking reaction of the DGEVA resin, FTIR transmission spectra were recorded before and after RICFP curing (Figure 3). The two intense peaks at 2930 and 2970 cm -1 can be attributed to the sp 3 C-H bond vibration of the aliphatic chain, [67] while the small ones at 3000 and 3060 cm -1 can be assigned to the methyl groups close to the epoxy rings.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47] The first work on RICFP was reported by Mariani et al In this work, a thick sample of 3,4-epoxycyclohexylmethyl 3,4epoxycyclohexanecarboxylate (CE) resin was successfully cured with dibenzoyl peroxide and iodonium salt in the formulation. [48] Later, Crivello, [49] Bomze et al, [42] Klicovts et al, [50] and, Svajdlenkova et al [51] further investigated this subject. All of them, however, used petroleum-based epoxy-resins.…”
Section: Introductionmentioning
confidence: 99%